Maternal and Fetal Outcomes of Hepatitis B Infection in Pregnant Women - Suchit Swaroop, Amar Deep; Mahvish Hashmi, Ajay Kumar (International Journal of Innovative Research in Medical Science, 2016)
Background: Little is known about the natural progression of the disease during pregnancy or its impact on pregnancy outcomes in women with hepatitis B virus (HBV) infection. Objective: To provide comprehensive details about the natural progression of HBV infection during pregnancy or its impact on pregnancy outcomes based on recent clinical reports. Search method: We searched from the Cochrane, Google scholar and PubMed by putting search item “maternal and fetal outcomes of hepatitis B infection in pregnant women”. We also searched the references list of relevant articles and contacted authors of retrieved studies. Data collection and analysis: Data were collected from the Medline and PubMed websites and analyzed by the expert gastroeneterologists and biologists.